Nickel Downstream and Indonesia’s Economic Diplomacy towards China - Fahik, Priscilla Rosalia; Putri, Annisa Dwida Sunggowo; Raharyo, Anggara (Jurnal Studi Diplomasi dan Keamanan, 2024)
Indonesia, a developing country rich in mineral resources, is pursuing a strategic nickel downstream industry policy to enhance its economy. This involves controlling nickel ore exports and promoting the establishment of smelters for processing. The research examines the implementation of this policy and its impact on Indonesia's economic relations with China. The study employs qualitative methods and applies Kishan S. Rana's economic diplomacy phases: Economic Salesmanship, Economic Networking, Image Building/Nation Branding, and Management Regulation & Resources. The enactment of Mineral and Coal Laws in 2014 and 2020 has influenced Indonesia's economic diplomacy with China. Key findings include Indonesia's shift from mining to smelter investment focus, exporting higher value-added nickel products, prioritizing EV battery industry development, and intensifying economic diplomacy efforts through investment and trade promotions. Special cluster units are playing an increasing role in this strategy.